Avaliação de bactérias epifíticas para silagem de grão de milho moído e reidratado - Silva, Yasmim Alvarenga (2022)
The aim of this study was to evaluate the effect of epiphytic strains previously isolated from rehydrated corn kernel silage (GMR) and selected based on desirable characteristics of the process on the chemical and microbiological characteristics of the silage. For the silage process, 21 strains were pre-selected from GMR. Ground corn (6 mm) was rehydrated to 64% dry matter (DM) and inoculated at a minimum rate of 108 CFU/kg of GMR. The corn kernel was compacted (5.03 kg) in 5L buckets until reaching an average density of 1005 kg.m-3. After compaction, mini-silos were sealed and weighed and it was opened after 60 days of storage. The experiment was conducted randomized block design (RBD) with 22 treatments, 21 strains and 1 control (without inoculants) with 3 replications, representing 3 blocks. Data were submitted to analysis of variance using the SISVAR® computational package. The means were compared using the Scott-Knott test at a 5% of significance. There was an effect of strains for the characteristics of pH, aerobic stability, DM, DM losses, starch, starch losses, crude protein, ammonia nitrogen (N-NH3), microorganism count and fermentation products. The control group, 221, 110, 189, 210, 185, 116, 7, 82 and 75 had higher N-NH3 (average: 0.1% MS). The lowest DM losses (%) were for silages inoculated with isolates 221 and 116 (1.95% on average for the group). The silages with the lowest starch losses were those inoculated with strains from group 77, 190, 110, 79 and 52 (average: 8.22%). The lowest pH values were recorded for silages treated with isolates 180 and 190 (average: 3.69). Strains 180, 190 and the control showed higher values of lactic acid, with an average of 4.72% of DM. Inoculation with strains 52, 189 and 185 increased the concentration of propionic acid in the silages (1.78% of DM on average). The lowest values of butyric acid were observed in treatments 180, 221 and 190 (0.09% of DM on average). Ethanol was higher in silage treated with strain 84 (1.04% DM). Strains 7, 52, 75, 77, 79, 82, 106, 110, 114, 126, 180, 190, 210 and 221 had higher lactic acid bacteria counts. Strains 82, 84, 104, 110 and 180 (1.71 log CFU/g silage on average) had the lowest counts of aerobic sporulating bacteria. The most efficient inoculants to reduce the yeast count were 82 and 108 (< 2.00 log CFU/g silage) and filamentous fungi strain 106. The strains that had the highest number of hours until their stability was broken were in groups 126 and 185 (92.3 h on average), followed by the group of strains 52, 26 and 114 (average: 75.3 h). Strains isolated from GMR silages have the potential to be used as inoculants and improve chemical and fermentative characteristics and aerobic stability.